(untitled) (Research, Society and Development, 2022)
Introduction: Palliative care corresponds to a type of therapeutic approach considering the individual as a whole and providing an improvement in the quality of life for him and for all those involved to minimize physical, psychological, social, and spiritual suffering. The Advance Directives of Will allow the individual to choose, still lucid and oriented, which care they wish to receive in their final moments of life. Objective: To analyze the effects of Advance Directives of Will in patients with terminal illness, to evaluate the quality of life and to identify the level of knowledge of the patient and of the professionals involved. Methodology: literature review, in 3 databases: Pubmed, Medline and Scielo using the health descriptors: “Advance Directives” AND “Palliative Care” AND “Aged”, “Quality of Life” AND “Advance Directives” and “Quality of Life” AND “Advance Directives” AND “Palliative Care”. The collection was carried out in October 2021 and the inclusion criteria were articles available in Portuguese, English or Spanish in national and international journals. The selected period was productions from the last 10 years (2011-2021). Results: For an understanding of the purpose of palliative care, communication is presented as essential, strengthening the links between the team, family members and patients. On the other hand, the lack of communication tends to generate distrust and insecurity in patients and their families. Randomized studies in developed countries that evaluated Advance Guidelines and quality of life found no differences in the quality of life of patients in the control arm and the intervention arm.